Carotid Ultrasound in Assessing Fluid Responsiveness in Patients with Hypotension and Suspected Sepsis. Issue 3 (September 2021) - Liteplo, Andrew S.; Schleifer, Jessica; Marill, Keith A.; Huang, Calvin K.; Gouker, Stacey K.; Ratanski, Daniel; Diamond, Eden; Filbin, Michael R.; Shokoohi, Hamid
ABSTRACT: Purpose: We sought to assess whether ultrasound (US) measurements of carotid flow time (CFTc) and carotid blood flow (CBF) predict fluid responsiveness in patients with suspected sepsis. Methods: This was a prospective observational study of hypotensive (systolic blood pressure < 90) patients "at risk" for sepsis receiving intravenous fluids (IVF) in the emergency department. US measurements of CFTc and CBF were performed at time zero and upon completion of IVF. All US measurements were repeated after a passive leg raise (PLR) maneuver. Fluid responsiveness was defined as normalization of blood pressure without persistent hypotension or need for vasopressors. Results: A convenience sample of 69 patients was enrolled. The mean age was 65; 49% were female. Fluid responders comprised 52% of the cohort. CFTc values increased significantly with both PLR ( P = 0.047) and IVF administration ( P = 0.003), but CBF values did not ( P = 0.924 and P = 0.064 respectively). Neither absolute CFTc or CBF measures, nor changes in these values with PLR or IVF bolus, predicted fluid responsiveness, mortality, or the need for intensive care unit admission. Conclusion: In patients with suspected sepsis, a fluid challenge resulted in a significant change in CFTc, but not CBF. Neither absolute measurement nor delta measurements with fluid challenge predicted clinical outcomes.